Envelope, please. And the award goes to… - Kohn, Donald B. (American Society of Hematology, 2014)
In this issue of Blood, Girard-Gagnepain et al report a potentially important discovery for improved gene transfer to human hematopoietic stem cells (HSCs) for gene therapy of blood cell diseases: a novel retroviral envelope to package (pseudotype) vectors for enhanced gene delivery to human HSCs.(1)